Comminution Flowsheet Energy Requirements of a New Narrow-Vein Mining Method - Judith George; Allan Cramm; Stephen Butt (Energies, 2025)
Narrow-vein deposits have historically been valuable in producing gold, tin, copper, silver, lead, and zinc. Developing these mineral resources is sometimes challenging due to economic and safety concerns. Given the small to medium scale of production, narrow-vein mining could be labor-intensive with increased exposure of the miners to hazardous conditions. A safe, mechanized, efficient, and sustainable method can be invaluable to operators looking to develop narrow-vein mineral resources. The comminution circuit (consisting of crushing and grinding) is downstream of most mineral resources’ extraction processes. Comminution is significantly energy-intensive, consuming almost half of the energy supplied to a mineral-processing activity. Thus, several engineers have investigated the continued development of sustainable narrow-vein mining and comminution technologies. This journal article focuses on a developed innovative, safe, mechanized, and continuous narrow-vein mining technology that has further made accessing narrow-vein deposits more economically feasible and efficient while reducing dilution of ores. The article also extensively presents the impact of this new mining approach on the daily production of the operation and the observed particle size distributions of the day-to-day operational output. Subsequently, the article evaluates and presents the impact of the new procedure of mineral extraction on the resultant size of the cuttings generated as well as the expected energy input of the comminution process downstream of the mining operation. The novelty of the mining method upon which this work is based is improved capital expenditure and reduced dilution. With the new mining method, otherwise-uneconomic narrow-vein deposits can be accessed.